Intraoperative conversion: it happens, we should smartly deal with it - Fourdrain, Alex; Leviel, Florent; Lafitte, Sophie; Berna, Pascal (Journal of Thoracic Disease, 2019)
Switching our approach intraoperatively from a minimally invasive to an open procedure, also known as intraoperative conversion, exist inherently since the implementation of the video-assisted thoracoscopic surgery (VATS). This intraoperative change of course has become a major concern especially with the spread of VATS in lung cancer surgery. Despite its prevention and because of its ineluctability, this intraoperative event is often seen as a complication or a failure, and remains somewhat of a taboo.